Mitochondria as a Potential Regulator of Myogenesis - Akira Wagatsuma; Kunihiro Sakuma (The Scientific World Journal)
Recent studies have shown that mitochondria play a role in the regulation of myogenesis. Indeed, the abundance, morphology, and functional properties of mitochondria become altered when the myoblasts differentiate into myotubes. For example, mitochondrial mass/volume, mtDNA copy number, and mitochondrial respiration are markedly increased after the onset of myogenic differentiation. Besides, mitochondrial enzyme activity is also increased, suggesting that the metabolic shift from glycolysis to oxidative phosphorylation as the major energy source occurs during myogenic differentiation. Several lines of evidence suggest that impairment of mitochondrial function and activity blocks myogenic differentiation. However, yet little is known about the molecular mechanisms underlying the regulation of myogenesis by mitochondria. Understanding how mitochondria are involved in myogenesis will provide a valuable insight into the underlying mechanisms that regulate the maintenance of cellular homeostasis. Here, we will summarize the current knowledge regarding the role of mitochondria as a potential regulator of myogenesis.